Curculigoside Protects against Titanium Particle-Induced Osteolysis through the Enhancement of Osteoblast Differentiation and Reduction of Osteoclast Formation - Fangbing Zhu; Jianyue Wang; Yueming Ni; Wei Yin; Qiao Hou; Yingliang Zhang; Shigui Yan; Renfu Quan (Journal of Immunology Research)
Wear particle-induced periprosthetic osteolysis is mainly responsible for joint replacement failure and revision surgery. Curculigoside is reported to have bone-protective potential, but whether curculigoside attenuates wear particle-induced osteolysis remains unclear. In this study, titanium particles (Ti) were used to stimulate osteoblastic MC3T3-E1 cells in the presence or absence of curculigoside, to determine their effect on osteoblast differentiation. Rat osteoclastic bone marrow stromal cells (BMSCs) were cocultured with Ti in the presence or absence of curculigoside, to evaluate its effect on osteoclast formation in vitro. Ti was also used to stimulate mouse calvaria to induce an osteolysis model, and curculigoside was administrated to evaluate its effect in the osteolysis model by micro-CT imaging and histopathological analyses. As the results indicated, in MC3T3-E1 cells, curculigoside treatment attenuated the Ti-induced inhibition on cell differentiation and apoptosis, increased alkaline phosphatase activity (ALP) and cell mineralization, and inhibited TNF-α, IL-1β, and IL-6 production and ROS generation. In BMSCs, curculigoside treatment suppressed the Ti-induced cell formation and suppressed the TNF-α, IL-1β, and IL-6 production and F-actin ring formation. In vivo, curculigoside attenuated Ti-induced bone loss and histological damage in murine calvaria. Curculigoside treatment also reversed the RANK/RANKL/OPG and NF-κB signaling pathways, by suppressing the RANKL and NF-κB expression, while activating the OPG expression. Our study demonstrated that curculigoside treatment was able to attenuate wear particle-induced periprosthetic osteolysis in in vivo and in vitro experiments, promoted osteoblastic MC3T3-E1 cell differentiation, and inhibited osteoclast BMSC formation. It suggests that curculigoside may be a potential pharmaceutical agent for wear particle-stimulated osteolysis therapy.